Freedom and mental health: an overview of the impact of fundamental rights on psychological wellbeing - Mohiyeddini, Changiz (Frontiers in Psychology, 2025)
Freedom, in its many forms, is a cornerstone of human rights. These include, among others, freedom of speech, freedom of thought, freedom of assembly, and freedom from discrimination. However, these freedoms are not only legal or political constructs but are also deeply embedded in the socio-cultural, religious, political, historical, and hence psychological composition of human beings. Rather than examining all of the many manifestations of freedom at once, this paper aims to explore the impact of a few specific freedoms—including freedom of speech, thought, assembly, movement, and protection from arbitrary arrest—on mental health and wellbeing. The objective of this commentary is to summarize existing evidence on how these freedoms support mental health and to highlight areas where the restriction of freedoms is linked to psychological distress, including anxiety, depression, and post-traumatic stress disorder. Furthermore, it also discusses the debilitating effects of self-censorship, discrimination, lack of access to education, and arbitrary detention on mental health. Despite substantial evidence underscoring the importance of freedoms for mental wellbeing, there remains a pressing need for comprehensive research to understand the complex associations between different aspects of freedom and their individual and collective impact on mental health. The discussion herein aims to provide a foundation for future studies and to inform policy interventions that protect both freedom and psychological wellbeing.